2002
DOI: 10.1128/mcb.22.22.7993-8004.2002
|View full text |Cite
|
Sign up to set email alerts
|

A Sperm-Associated WD Repeat Protein Orthologous to Chlamydomonas PF20 Associates with Spag6, the Mammalian Orthologue of Chlamydomonas PF16

Abstract: cDNAs were cloned for the murine and human orthologues of Chlamydomonas PF20, a component of the alga axoneme central apparatus that is required for flagellar motility. The mammalian genes encode transcripts of 1.4 and 2.5 kb that are highly expressed in testis. The two transcripts appear to arise from alternative transcription start sites. The murine Pf20 gene was mapped to chromosome 1, syntenic with the location of the human gene on chromosome 2. An antibody generated against an N-terminal sequence of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
114
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 38 publications
(53 reference statements)
3
114
0
Order By: Relevance
“…We discovered that this gene encodes two different proteins, which are expressed in different patterns and have different subcellular localizations in male germ cells. The PF20 proteins contain contiguous WD repeats in their C termini, suggesting that these molecules interact with other proteins, a notion substantiated in our previous work, which demonstrated that PF20 binds to SPAG6 (16). Targeted disruption of Pf20 sequences encoding the C terminus of both proteins resulted in severe impairment of spermatogenesis and disorganization of sperm flagellar structure.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…We discovered that this gene encodes two different proteins, which are expressed in different patterns and have different subcellular localizations in male germ cells. The PF20 proteins contain contiguous WD repeats in their C termini, suggesting that these molecules interact with other proteins, a notion substantiated in our previous work, which demonstrated that PF20 binds to SPAG6 (16). Targeted disruption of Pf20 sequences encoding the C terminus of both proteins resulted in severe impairment of spermatogenesis and disorganization of sperm flagellar structure.…”
supporting
confidence: 48%
“…To understand the function of the central apparatus in mammals, we cloned the human and mouse orthologues of Chlamydomonas, PF16 (SPAG6) (14,15) and PF20 (16). SPAG6-deficient mice are hydrocephalic, and males surviving to maturity are infertile as a result of a marked sperm motility defect associated with disorganization of flagellar structures, including loss of the central pair microtubules and disorganization of the outer dense fibers and fibrous sheath (6).…”
mentioning
confidence: 99%
“…As described previously, SPAG16L protein was also localized in the cytoplasm of SPAG16L/ pEGFP-N 2 plasmid transfected CHO cells [2], similar to the distribution pattern of TSSK2. To further study the association of the two proteins, TSSK2/DsRed-N 1 and SPAG16L/pEGFP-N 2 were co-transfected into CHO cells and the localization of each protein was examined by confocal microscopy.…”
Section: Interaction Of Spag16l and Tssk2mentioning
confidence: 69%
“…A mouse testis cDNA library was screened using the C-terminus domain of SPAG16 as the bait [2]. Plasmid DNA from the positive yeast clones was sequenced, and the candidate interacting genes were identified by searches of public databases.…”
Section: Potential Proteins That Associate With Spag16mentioning
confidence: 99%
See 1 more Smart Citation